IMPLEMENTATION OF FISHING LABORERS’ INCOME SHARING FROM AN ISLAMIC ECONOMIC PERSPECTIVE: A CRITICAL ANALYSIS ON BAJOE FISHING LABORERS, BONE REGENCY - Muh. Nurham; Arifin S (Jurnal Ilmiah Al-Tsarwah, 2025)
This study aims to analyze the income distribution mechanism of fishermen workers in Bajoe, Bone Regency, and to evaluate the implementation of this income distribution from the perspective of Islamic Economics. The research method employed is qualitative with a field research approach, supported by phenomenological, sociological, and economic perspectives. Primary data were collected through in-depth interviews with fishermen workers and boat owners in Bajoe, while secondary data were obtained from comprehensive literature studies. The findings indicate that the income distribution mechanism in Bajoe remains traditional, verbal, and without written contracts, relying on trust and hereditary customs with a profit-sharing model based on hierarchical positions aboard the vessel. From the perspective of Islamic Economics, this practice is not yet fully aligned with the principles of Sharia, such as justice (al-‘adl), clarity (bayan), and transparency. The absence of written agreements and the lack of transparency in calculating profits and operational costs make fishermen workers vulnerable to structural injustice.